2024
DOI: 10.1371/journal.pone.0295550
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of chloroplast genomes of seven Juniperus species from Kazakhstan

Shyryn Almerekova,
Moldir Yermagambetova,
Smatulla Jumanov
et al.

Abstract: Juniperus species are shrubs or trees in the family Cupressaceae that play an important role in forest ecosystems. In this study, we report the complete sequences of the plastid (pt) genomes of five Juniperus species collected in Kazakhstan (J. communis, J. sibirica, J. pseudosabina, J. semiglobosa, and J. davurica). The sequences of the pt genomes of the five species were annotated in addition to two full pt genome sequences from J. sabina and J. seravschanica, which we have previously reported. The pt genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Moreover, our examination of nucleotide diversity demonstrated similar variability in other species. For instance, Liu et al [48] and Almerekova et al [49] identified variability in the accD region among Quercus and Juniperus species, respectively. Rodda and Niissalo [50] observed variability in the accD and ndhF regions within Hoya species plastomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our examination of nucleotide diversity demonstrated similar variability in other species. For instance, Liu et al [48] and Almerekova et al [49] identified variability in the accD region among Quercus and Juniperus species, respectively. Rodda and Niissalo [50] observed variability in the accD and ndhF regions within Hoya species plastomes.…”
Section: Discussionmentioning
confidence: 99%